2021
DOI: 10.3390/ijms22189817
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRα Enhanced Infection of Breast Cancer Cells with Human Cytomegalovirus but Infection of Fibroblasts Increased Prometastatic Inflammation Involving Lysophosphatidate Signaling

Abstract: Human cytomegalovirus (HCMV) infects 40–70% of adults in developed countries. HCMV proteins and DNA are detected in tumors and metastases, suggesting an association with increased invasion. We investigated HCMV infection in human breast cancer cell lines compared to fibroblasts, a component of tumors, and the role of platelet-derived growth factor receptor-α (PDGFRα). HCMV productively infected HEL299 fibroblasts and, to a lesser extent, Hs578T breast cancer cells. Infection of another triple-negative cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
(107 reference statements)
1
9
0
Order By: Relevance
“…In experiments with cultured cells, we showed that the level of HCMV infectivity of different breast cancer cell lines was much lower than in fibroblasts. This did not depend on whether the breast cancer cells were triple negative or hormone receptor positive [ 59 ]. Instead, infection levels depended on the expression of PDGFRα.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments with cultured cells, we showed that the level of HCMV infectivity of different breast cancer cell lines was much lower than in fibroblasts. This did not depend on whether the breast cancer cells were triple negative or hormone receptor positive [ 59 ]. Instead, infection levels depended on the expression of PDGFRα.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these discrepancies in the detection of HCMV in breast tumors could also be due to variability in the cellular composition of the breast tumors. We recently showed that the incidence of HCMV infection of breast cancer cells is considerably less than that of fibroblasts with higher infection dependent on the expression of platelet-derived growth factor receptor alpha (PDGFRα) [ 59 ]. Fibroblasts are a component of the microenvironment and they are likely to be infected more than the breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…One of known human viral receptor genes, PDGFRA , was included in genes under positive selection in P. larvata. PDGFRA can activate mutations in gastrointestinal stromal tumors [ 68 ] and is required for human cytomegalovirus infection [ 69 , 70 ]. There has been no study focus on the PDGFRA receptor in masked palm civets, and further study is needed.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to bacteria, there is also evidence showing a potential relationship of viral infection with breast cancer. Infection with human cytomegalovirus (CMV) is common in adults in developed countries (~40-70%), and this virus was shown to preferentially infect breast cancer cells with elevated expression of platelet-derived growth factor receptorα (PDGFRα) and fibroblasts (which have high levels of PDGFRα expression); infection of PDGFRα + fibroblasts raised the possibility that human CMV infection could affect the tumor microenvironment, leading to a more inflammatory milieu [110]. Previous research also reported some conflicting data of the potential roles of HPV, EBV, or MMTV in breast cancer, but the precise roles of these viruses in breast tumorigenesis remain unclear [111,112].…”
Section: Microbes In Breast Tissue and Cancermentioning
confidence: 99%